Search for a supersymmetric partner to the top quark in final states with jets and missing transverse momentum at √s=7TeV with the ATLAS detector - Alonso, Francisco (2012)
A search for direct pair production of supersymmetric top squarks (t 1) is presented, assuming the t1 decays into a top quark and the lightest supersymmetric particle, χ10, and that both top quarks decay to purely hadronic final states. A total of 16 (4) events are observed compared to a predicted standard model background of 13.5-3.6+3.7(4.4-1.3+1.7) events in two signal regions based on Ldt=4.7fb-1 of pp collision data taken at √s=7TeV with the ATLAS detector at the LHC. An exclusion region in the t1 versus χ10 mass plane is evaluated: 370<mt1<465GeV is excluded for mχ10∼0GeV while mt1=445GeV is excluded for mχ10≤50GeV.